Export competitiveness and domestic productivity facets: case of Lithuania - Travkina, Irina; Tvaronavičienė, Manuela (Journal of Business Economics and Management, 2011)
The relationships between export competitiveness and separate productivity factors are complex. Since the late 1990s debates on these relationships have been strongly influenced by the Krugman hypothesis, which states that the competitiveness could be measured directly by productivity. In the paper it is assumed, that export competitiveness is derivative of main factors’ productivities, therefore properly presented and juxtaposed data on labour, capital and energy productivity/intensity would provide with new insights about character of relations between export competitiveness and main production factors productivities. Practical approach for predicting the Lithuanian export competitiveness future change direction by using listed indicators is being suggested. As a result, possible implications of main productivity factors impact on further export competitiveness have been foreseen. Article in English. Lietuvos eksporto konkurencingumas ir šalies produktyvumo dėmenys Santrauka. Straipsnyje analizuojami eksporto konkurencingum lemiantys atskiri gamybos veiksniai. Atlikus Lietuvos pramones šaku pagrindiniu gamybos veiksniu-darbo, kapitalo ir energijos produktyvumo/ intensyvumo rodikliu lyginamj analizê, padaryta prielaida, jog reikalingi sprendimai, kurie padetu pramones šakoms atrasti efektyvu kompleksišk minetu gamybos ištekliu naudojimo bud bei prisidetu prie pramones eksporto konkurencingumo didinimo. Atlikto tyrimo praktinê vertê lemia kelios aplinkybes: pirma, pasiulytos naujos ižvalgos apie pramones eksporto konkurencingumo vertinim; antra, nustatytos tolesniu eksporto konkurencingumo teorijos tyrimu sritys. Reikšminiai žodžiai: tarptautine prekyba, eksporto konkurencingumas, produktyvumas, intensyvumas.